Mastering Modern World History - Lowe, Norman (New York Palgrave Macmillan, 2007)
"The fourth edition of this leading book is for students taking a first course in Modern World History and for undergraduates in History and International Relations. It is a complete, readable, self-contained course, suitable for individual study or classroom use and requires no previous knowledge."--Jacket.
Include Pictures, Maps and Index
Keywords: History, Modern -- World history